Isolation of chemical components from the methanol extract of dracaena umbratica leaves and the heartwood of shorea bracteata / Zaini Yusoff - Yusoff, Zaini (2010)
Tropical rainforests are the most biologically diverse ecosystems on earth and are home to around 80% of its biodiversity. The tropical rainforests have been called the "Jewels of the Earth", and regarded as the "world's largest pharmacy", This is because over 25 percent of natural medicines have been discovered in these forests. Malaysia is one of the countries blessed with a luxurious, most diverse tropical forest ecosystem with large amount of natural resources. The forests in Malaysia are mostly dominated by trees from the Dipterocarpaceae family (95%),hence they are termed as 'dipterocarp forests'. The dipterocarp forest occurs on dry land just above sea level to an altitude of about 900 metres. The most common tree species found in this forest include, Anisoptera, Dipterocarpus, Dryobalanops, Hopea, Shorea and Parashorea. Many are large forest emergent species, typically reaching heights of 40-70 m tall, some even over 80 m (in thegenera Dryobalanops, Hopea and Shorea). The species of this family are of major importance in the timber trade.